Penatalaksanaan Restorasi Kelas II GV Black Resin Komposit dengan Matriks Tofflemire - Fikri Nabila; Juwita Raditya Ningsih (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Background: Class II restoration according to the classification of Greene Vardiman Black is one of the procedures in dental conservation that often presents a challenge for operators or dentists during treatment. Class II restorations have their own level of difficulty, particularly during the placement of restorative materials into the cavity. One of the possible failures in Class II restorative treatment is marginal leakage, which can lead to microleakage at the restoration margins. Purpose: To report the success of class II restoration with composite resin using tofflmire matrix. Case report: A 23-year-old female patient came with a complaint of cavities, the complaint was felt since 1 year ago in the lower left back tooth, there was no pain and had never been treated. In the case, preparation and restoration were carried out using composite resin with isolation using tofflmire matrix, applied using an Incremental technique. Discussion: Class II posterior tooth restorations have challenges such as leakage due to the techniques and materials used. Composite resin is chosen because of its good adaptation, esthetics, and wear resistance. Incremental techniques are preferred because they reduce polymerization stress and provide optimal curing results. Tofflemire matrix is ​​used for stability and soft tissue protection.Conclusion: The selection of composite resin with an Incremental technique and the use of a Tofflemire matrix provides more optimal, aesthetic, and minimal risk of failure results for class II posterior tooth restorations.